Characterization of the Emerging Enteropathogen Escherichia Albertii Isolated from Urine Samples of Patients Attending Sapporo Area Hospitals, Japan - Miyuki Fujioka; Sho Yoshioka; Masahiko Ito; Chowdhury Rafiqul Ahsan (International Journal of Microbiology)
Recently, Escherichia albertii has been identified as a causative agent of diarrhea in humans and is often misidentified as diarrheagenic Escherichia coli (DEC), a lactose-nondegrading bacterium. In this study, we performed biochemical characterization, gene possession status, drug susceptibility testing, and sequencing analysis of the strains detected in urine samples. One urea-degrading strain was detected in terms of biochemical characteristics, but was found to be nonurea-degrading by another method, leading to conflicting results. All target strains possessed the E. albertii-specific gene, the DEC common gene eae, and the E. coli 16S rRNA gene. In the drug susceptibility test, all urine-derived strains were sensitive to tetracycline (TC), whereas the JCM 17328 strain was resistant to TC, suggesting that TC is effective against urine-derived E. albertii strains. In 16S rRNA sequencing analysis, the E. albertii strains were ranked at the top of homology, but not in the top one, making it difficult to differentiate them from other strains. In summary, if a suspected lactose-nondegrading E. coli strain was isolated from a urine sample, it could be differentiated from E. albertii by the presence of E. albertii-specific genes.